Evaluating Antioxidant Performance, Biosafety, and Antimicrobial Efficacy of Houttuynia cordata Extract and Microwave-Assisted Synthesis of Biogenic Silver Nano-Antibiotics - Kavya Moorthy; Kai-Chih Chang; Hsiao-Chi Huang; Wen-Jui Wu; Cheng-Kang Chiang (MDPI AG, 2023)
From the traditional Chinese medicine point of view, although Houttuynia cordata extract (HCE) possesses an incredible amount of phytonutrients and exhibits antioxidant activities, excessive doses of HCE can cause danger to organisms and lead to death. In this study, we first examine HCE's overall phenolic and flavonoid content, antioxidant efficacy, and antibacterial activity. Results show that HCE is suitable as a bio-reducing agent for the microwave-assisted synthesis of silver nanoparticles (HCE-AgNPs) with enhanced antioxidant and antimicrobial performance. Under an optimized microwave condition (i.e., 100 °C for 10 min), the HCE-stabilized AgNPs were confirmed with a UV-visible peak at 430 nm and 19.7 ± 4.2 nm in size. Physicochemical properties of HCE-AgNPs were extensively characterized by zeta-potential, FT-IR, XRD, and XPS measurements. Compared to the HC extract counterpart, HCE-AgNPs display superior antioxidant activity, higher DPPH scavenging efficiency, and enhanced broad-spectrum bactericidal activity to inhibit the growth of all tested bacterial strains at doses of 2 μg/mL. Biosafety evaluation indicated that HCE-AgNPs are noncytotoxic on human red blood cells. These data show that the microwave synthesis of AgNPs exhibits a great antioxidant ability, superior antibacterial activity, and a trivial hemolytic effect, providing another bactericidal therapy strategy to address the increasing healthcare-associated infections.